LEVELS OF FORMALITY IN OBAMA™S INTERVIEW AND SBY™S INTERVIEW - Br Karo, Seftyani Fransiska; Tangkas, I Wayan Dirgayasa (TRANSFORM: Journal of English Language Teaching and Learning, 2012)
This study was intended to describe levels of formality used by Obama and SBY in their interviews.  This  study  was  carried  out  with  descriptive  research.  The  data  were collected with documentary technique and the instrument used was documentary sheet. The data were analyzed by descriptive comparative. The result of the research show that Obama tends to use Casual level (44,78%),  Formal (29,05%), Consultative (26%), and Intimate (0,17%) while SBY tends to use Formal level (49,20%), Frozen (3,16%), Consultative (34%) and Casual (13,83%). So, in speaking Obama is more friendly because sometimes he did  a joke and laugh while SBY is more serious to answer or to response the interviewer™s questions. It is hoped that the result of this study is useful to everyone who wants to study about levels of formality.   Key words : Levels of Formality, Obama™s Interview, SBY™s Interview